Rola kultury hip-hop w kształtowaniu się tożsamości młodzieży – wybrane konteksty - Bieńkowska, Monika (Studia Edukacyjne, 2018)
This article was developed on the basis of my master’s thesis on hip-hop culture as a factor shaping young people’s identity. In today’s world, young people are increasingly looking for ways to express themselves and their values, which may be associated with belonging to different types of subcultures. Growing individuals manifest their independence by disagreeing with the surrounding reality and defying the prevailing social principles. It seems appropriate to belong to a chosen youth subculture. I will devote my attention to the subculture originating among the black Americans, namely the hip-hop subculture. The rap environment is very often associated with a pejorative phenomenon, vulgarisms, blockers derived from the social margin. In today’s times, in the era of ubiquitous openness and availability of mass media, in the consumer-oriented environment, hip-hop has become a part of the lives of most young, adolescent audiences. The article will also present the development of hip-hop culture in Poland and around the world, as well as the effects that it brought in the process of shaping the identity of young people.